Stringing Beads Therapy: Alternatif Tindakan Dalam Menjaga Mental Health Santriwati Pondok Pesantren Salafiyah Putri Al Ishlahiyah Kota Malang - Rini, Ajeng Setyo; Setyawati, Cindy Angga; Umah, Devi Nikmatul; Sholihah, Wildan Nurus; Untari, Sri (Journal Of Human And Education (JAHE), 2024)
The strict rules in pesantren often cause students to feel pressured and experience stress. The environment and educational methods in pesantren are considered as stressors that can affect the physical and psychological conditions of students in a certain period of time. As a result, students experience various problems such as fatigue, headaches, boredom, anxiety, and difficulty in managing time. The stress experienced by students has a negative impact on their ability to manage time due to unstable emotional conditions. The program “Stringing Beads Therapy: An Alternative Action in Maintaining the Mental Health of Female Students” was implemented at the Salafiyah Pesantren Al-Islahiyah with the aim of reducing the effects of stress on female students. Through creative stringing activities, this program also aims to foster an entrepreneurial spirit among female students in order to create business power for each female students. In addition, this service program also aims to provide insight into the importance of maintaining mental health through good time management. The method used is participatory which emphasizes the full participation of activity participants. The results of the activity showed significant positive impacts, including increased relaxation, stress reduction, and a better understanding of the importance of maintaining mental health. This activity also creates economic opportunities through the products produced, and inspires female students to be more active in entrepreneurship